Social facilitation and human-computer interaction. - Hall, Byron; Henningsen, David Dryden (Computers in Human Behavior, 2008)
The Computers As Social Actors (CASA) research paradigm has examined how individuals respond to computers programmed to interact in various ways. In the current research, we extend the principles of CASA to determine whether computer icons can be used to produce social facilitation effects. Varying task difficulty and the presence or absence of a computer icon (i.e., Microsoft word's Clip), performance on a typing task is considered. Overall, results provide some support for the contention that the mere presence of a computer icon may influence task performance. Copyright (c) 2008 Elsevier Ltd.